Lucky bastard : my life, my dad, and the things I'm not allowed to say on TV - Buck, Joe; Rosenberg, Michael (Dutton, 2016)
"In his debut memoir, Joe Buck talks about his life, his career, and his memorable relationship with his father, legendary sportscaster Jack Buck,"--Baker & Taylor.